Enzyme-catalyzed kinetic resolution of spirocyclic secondary amines obtained by ring-closing metathesis, as well as synthesis of cyclopentane[c]pyrrole and -pyridines by the Pauson-Khand reaction - Özdemirhan, Devrim; Buhlak, Shafeek; Koç, Durukan (European Journal of Chemistry, 2025)
As herein defined; a ring closing metathesis (RCM) reaction of N-anchored homoallylic dienes followed by enzymatic kinetic resolution and ring closing enyne metathesis (RCEM) with an intramolecular Pauson-Khand reaction of N-tethered homopropargylic enynes are described for the first time. RCM afforded azaspirodeca and -undecadiene with 78 and 82% chemical yields, as well as azaspironona and decadienecarboxylates with 65 and 70% chemical yields, respectively. Furthermore, RCEM protocol resulted in conjugated diene 50% chemical yield. Moreover, intramolecular Pauson-Khand reaction is also applied to enynes, which yielded cyclopenta[c]pyrrole-carboxylate as diastereomeric mixtures; besides cyclopenta[c]pyridin-one and cyclopenta[c]pyridin-carboxylate frameworks as single diastereomers. Above all, secondary amines (azaspirodeca and undecadiene) have been efficiently resolved through an enzyme-catalyzed reaction in a moderate ee up to 77 and 20% ee, with their corresponding esters up to 75 and 55% ee, in the presence of CAL-B (being the most effective biocatalyst) and recombinant from Aspergillus oryzae. Both CAL-B and CAL-A-CLEA afforded reverse enantiomeric separation of them for the first time.